Exploring the climate sensitivity of tourists to South Africa through TripAdvisor reviews. Issue 1 (2nd January 2019) - Fitchett, Jennifer M.; Hoogendoorn, Gijsbert
ABSTRACT: Climate is considered a key determinant of where and when tourists travel, and their enjoyment of the trip. Climate change threats to tourism include sudden damages from natural disasters, and more gradual changes in temperature, precipitation amount and seasonality, sunshine hours and humidity. Tourism Climatic Indices (TCI) consider the latter, classifying the contemporary suitability of destinations for tourism, and projecting changes in suitability under climate change. Scores are seldom compared to tourists' objective experiences of climate during vacations, or tourists' sensitivity to climate. This study assesses 5898 TripAdvisor reviews to determine the frequency of climate mentions in unstructured reviews, and the distribution of climate mentions relative to the TCI. These findings are compared to TCI results for 19 destinations in South Africa. A total of 464 TripAdvisor reviews, accounting for 7.9% of the sample, mentioned climatic conditions, highlighting the climatic suitability of South Africa for tourism. The distribution of climatic conditions mentioned in these reviews largely aligns with the TCI, but slight modifications particularly for wind speed are suggested for an improved modelling in the South African context. TripAdvisor reviews are argued to provide a valuable source of information for the tourism sector to facilitate effective adaptation to climate change.